Membangun Tradisi Literasi Anti Korupsi di Kalangan Elite Daerah dalam Perspektif Hukum Tata Negara - Darmadi Djufri (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: Corruption has a very negative impact. As a crime, corruption not only harms the country's finances and economy, but also hampers the growth and continuity of national development which demands high effectiveness. Methodology: Corruption has eroded democratic values, violated the principles of good governance, and caused discrimination against public services. Corruption has also led to low openness and representativeness in the formulation of policies in the legislature, and even corruption has hampered legal certainty in the judiciary. Results: Corrupt behavior among regional elites still occurs because: 1. System factors, especially regulations related to political recruitment through regional elections, where the weaknesses include our laws that still allow candidates who are suspects in legal cases to run for regional heads, which are further strengthened by the dominance of the ideology of materialism and capitalism that supports these elections, so that the elections still have the opportunity to give birth to corrupt officials, 2. Political actor factors, the low integrity, credibility, and capacity of candidates for regional heads are the biggest contributors to the emergence of corrupt governments, the morality of the candidates is only hunting for the results, namely the seat of power, even though by using all means. The ruling is not to serve the people but to seek material gain.